Cellulose-based fluorescent materials fabricated in CO2 switchable solvent for freshness monitoring. (1st February 2023) - Sun, Yi; Zhang, Wei; Lu, Shan; Miao, Wenhua; Chen, Meiling; Liu, Fei; Na, Haining; Zhu, Jin
Abstract: Herein, a novel cellulose-based fluorescent material with amine-responsive property was developed in a CO2 switchable solvent for the contactless, real-time, and visual monitoring of the freshness of shrimp, crab, and fish. A nucleophilic cellulose carbonate intermediate is in-situ formed upon dissolution of cellulose in the CO2 switchable solvent, which is adopted for the highly effective grafting of poly(l -lactic acid) and amine-responsive fluorescent reagent 7-amino-4-(trifluoromethyl) coumarin onto the cellulose backbone via ring opening polymerization and nucleophilic substitution reaction, respectively. The product has good processibility, and sensitive and reversible fluorescent responsive towards ammonia. The fluorescent intensity of the material decreased significantly and its fluorescent color changed from blue to cyan, when the aquatic products got spoiled. This study indicates that the CO2 switchable solvent has great potential for the modification of cellulose with various functionality by taking advantage of the highly active nucleophilic cellulose carbonate intermediate. Graphical abstract: Cellulose was homogeneously modified in CO2 switchable solvent with poly(l -lactic acid) and 7-amino-4-(trifluoromethyl) coumarin to fabricate amine-responsive fluorescent materials with good processibility for real-time and visual monitoring of the freshness of aquatic products. Unlabelled Image